PENERAPAN PRINSIP-PRINSIP ANIMASI PADA FILM SERIAL ANIMASI “FICUSIA” EPISODE 1 - Zega, Selly Artaty; Hidayah, Arifatul (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2023)
This research was conducted to identify the implementation of animation principles in the first episode of Ficusia the animated series. The purpose of this study is to provide an explanation for the application of the principles in the animated series. This is qualitative research with a descriptive approach. The source of data in this study came from interviews with several animation experts who understand the principles of animation principles. Data were also obtained from various books, journals, and papers that discuss the principles of animation. The results of this study illustrate the implementation of animation principles in the first episode of Ficusia the animated series, and show how the application of animation principles in this episode can make it feel livelier to achieve the more interesting result.